2016
DOI: 10.1007/s11126-016-9426-2
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Impact of Cannabis on Doses of Discharge Antipsychotic Medication in Individuals with Schizophrenia or Schizoaffective Disorder

Abstract: Patients with schizophrenia or schizoaffective disorder have a high prevalence of comorbid cannabis use disorder (CUD). CUD has been associated with poorer outcomes in patients. We compared doses of antipsychotic medications at the time of discharge from hospital among inpatients with schizophrenia or schizoaffective disorder with or without concurrent cannabis use. We reviewed the medical records of patients (N = 8157) with schizophrenia or schizoaffective disorder discharged from the hospital between 2008 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…We were able to exclude additional substance abuse as a moderating factor. Previous studies (28,29) showed a mitigating effect of comorbid substance use in psychotic patients on CPZ dosages. Nevertheless, this effect disappeared when controlling for sociodemographic data and length of stay.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We were able to exclude additional substance abuse as a moderating factor. Previous studies (28,29) showed a mitigating effect of comorbid substance use in psychotic patients on CPZ dosages. Nevertheless, this effect disappeared when controlling for sociodemographic data and length of stay.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, it is conceivable that the effect also loses impact with a certain degree of severity of the disease. It has to be taken into account that previous studies (28,29) included all patients of a hospital, while the present study focuses exclusively on legally accommodated and thus more severely affected patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though in vivo data on these drug interactions are limited, cannabis smoking cessation is among the implications of two cases of intoxication with CYP1A2 substrates (clozapine and olanzapine). 62 , 63 The subsistence of adverse reactions from cannabis–drug interactions remain unknown, and merit future study.…”
Section: Discussionmentioning
confidence: 99%